1994
DOI: 10.3758/bf03209256
|View full text |Cite
|
Sign up to set email alerts
|

Reflections of the mirror effect for item and associative recognition

Abstract: In five experiments, participants studied pairs of words and yes/no recognition memory for both item and associative information was tested. Two stimulus manipulations, nouns versus nonnouns and high versus low word concreteness, produced the mirror effect for both item and associative recognition. The mirror effect was reflected in both measures of accuracy and response latency. A word frequency manipulation, however, produced the mirror effect only for item recognition. Two additional experiments showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 48 publications
(83 reference statements)
8
74
1
1
Order By: Relevance
“…In contrast to serial and free recall, the most common finding in item recognition memory is that LF words are recognized better, showing more hits and fewer false alarms than HF words (Clark, 1992;Glanzer & Adams, 1990Hockley, 1994;MacLeod & Kampe, 1996;Malmberg & Murnane, 2002;Reder et al, 2000;Schulman, 1967). At first blush it might seem that this effect is inconsistent with the proposal for an encoding advantage for HF words.…”
Section: Effects Of Word Frequency On Item Recognitioncontrasting
confidence: 46%
See 2 more Smart Citations
“…In contrast to serial and free recall, the most common finding in item recognition memory is that LF words are recognized better, showing more hits and fewer false alarms than HF words (Clark, 1992;Glanzer & Adams, 1990Hockley, 1994;MacLeod & Kampe, 1996;Malmberg & Murnane, 2002;Reder et al, 2000;Schulman, 1967). At first blush it might seem that this effect is inconsistent with the proposal for an encoding advantage for HF words.…”
Section: Effects Of Word Frequency On Item Recognitioncontrasting
confidence: 46%
“…Associative learning is more demanding because it requires the encoding of each item, as well as binding the two items together; in our view, each of these operations draws on the same limited resource pool. Consistent with this idea, multiple experiments have demonstrated that pairs (Chalmers & Humphreys, 2003;Clark, 1992, Experiment 1;Clark & Shiffrin, 1992) or triplets (Clark, 1992, Experiment 2) of HF words are easier to recognize than pairs or triplets of LF words (although see Hockley, 1994 for a null effect). For example, Clark (1992) tested item recognition, pair recognition and free recall for the same items studied in triplets.…”
Section: Effects Of Word Frequency On Associative Recognitionmentioning
confidence: 63%
See 1 more Smart Citation
“…This pattern of the picture superiority effect for associative recognition also stands in contrast with other types of stimulus comparisons that have been made in tests of associative recognition. A mirror pattern has been observed in associative recognition for comparisons between words versus letter strings and pseudowords (Greene, 1996(Greene, , 2004, concrete versus abstract words (Hockley, 1994), words versus unfamiliar faces (Criss & Shiffrin, 2004;, and words versus Chinese characters . Why do these stimulus comparisons result in a mirror pattern in tests of associative recognition, whereas line drawings versus words do not?…”
Section: Resultsmentioning
confidence: 99%
“…As was noted previously, the picture superiority effect in tests of item recognition is typically observed as a mirror pattern in which the advantage for pictures is seen in both a higher hit rate and a lower false alarm rate (Glanzer & Adams, 1985). A mirror pattern has been found in tests of associative recognition for several different types of stimulus comparisons: words versus letter strings (Greene, 1996), words versus pseudowords (Greene, 2004), concrete versus abstract words (Hockley, 1994), words versus unfamiliar faces (Criss & Shiffrin, 2004;, and words versus Chinese characters . Words and line drawings represent another type of stimulus comparison and, on the basis of the above findings, it was expected that if associations formed between items from one type of stimulus class were more memorable than associations between items of the other stimulus class, then this advantage would also be seen as a mirror effect.…”
mentioning
confidence: 81%